Collagen polymorphism in normal and cirrhotic human liver. - Seyer, J M (1977)
Collagens in normal human liver and in alcoholic cirrhotic liver were investigated. Collagens were solubilized by limited proteolysis with pepsin under nondenaturing conditions, and after purification, were fractionated into types I and III by selective precipitation with NaCl. After carboxymethyl cellulose and agarose chromatography, the resulting alpha-chains from each of the collagen types were analyzed with respect to their amino acid and carbohydrate compositions. A comparison of the results obtained from normal liver with those from the diseases organ revealed no significant differences. The isolated human liver alpha1(I) and alpha1(III) chains were digested with CNBr and the generated peptides were separated and purified by a combination of ion-exchange and molecular sieve chromatography. The molecular weight and the amino acid and the carbohydrate compositions of each of the peptides were identical to those of the corresponding human skin peptides except for the slightly higher content of hydroxylysine in some of the peptides. The relative content of type III in relation to type I collagen in both normal anc cirrhotic liver was determined by digesting washed liver homogenates directly with CNBr and quantitating the resultant alpha1(I) and alpha 1(III) peptides after chromatographic separation. The relative quantities of these peptides indicated that normal human liver contained an average of 47% type III, with the remainder being type I. Cirrhotic liver, on the other hand, contained a significantly smaller proportion of type III, ranging from 18 to 34% in different samples, with a corresponding increase in type I. These findings indicate that although the amino acid and carbohydrate compositions of collagens deposited in cirrhotic liver are normal, the fibrotic process of alcoholic liver disease in humans is accompanied by an alteration in tissue collagen polymorphism, and suggest that the observed alterations may have pathogenetic implications.